Localmassa Pvt Ltd : Mussels' Sand / Izzat Iskandar Noor Alhazly ...[et al.] - Noor Alhazly, Izzat Iskandar; Wan Ibrahim, Syed Muhammad Amirul; Aidi Azha, Nurqistina Izzati; Mohd Din, Nur Diana Nadhirah (2019)
The initiation of our product comes from the idea of sustainable products that can help to reduce waste and save the environment. Not only it is eco-friendly, it is also much more reasonable and easier to be obtained. Our company guarantees our invention can change the society's perspective in viewing the capability of an unwanted waste.